OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY FOR THE DETECTION OF SECONDARY CHOROIDAL NEOVASCULARIZATION IN VITELLIFORM MACULAR DYSTROPHY. Issue Volume 14:Issues 1(2020) (2020) - Stattin, Martin; Ahmed, Daniel; Glittenberg, Carl; Krebs, Ilse; Ansari-Shahrezaei, Siamak
Abstract : Purpose: Optical coherence tomography angiography (OCTA) is used to assess vascular abnormality in advanced stage vitelliform macular dystrophy (VMD2). Methods: Multimodal imaging including spectral domain (SD) OCT, autofluorescence (AF), fluorescein (FA) and indocyanine green angiography (ICGA) as well as optical coherence tomography angiography were performed. Patients: Two eyes in one young patient with diagnosed vitelliform macular dystrophy were investigated for progressive visual dysfunction. Results: Optical coherence tomography angiography identified neovascular formation within the outer retina and the choriocapillaris respectively while all other imaging methods were inconclusive. Conclusion: Optical coherence tomography angiography was superior to conventional angiography in the detection of choroidal neovascularization (CNV) in advanced retinal disorders like vitelliform macular dystrophy. Abstract : OCTA identified morphological changes including different CNV formation in severely altered retinal structures like advanced stage VMD2 in contrast to conventional imaging technology. The practical value gained herein may facilitate our understanding of CNV biomarkers in OCTA.